Perempuan dan Revolusi: Analisis Tanda Terkait Perempuan dalam Naskah Drama "Domba-domba Revolusi" Karya B. Soelarto: Women and Revolution: Analysis of Signs Related to Women in “Domba-domba Revolusi” by B. Soelarto - Adi Mas'ud, Muhammad Azhar (Jurnal Pena Indonesia, 2025)
The play script “Domba Domba Revolusi” by Bambang Soelarto contains many signs related to women, especially related to the revolution. For this reason, the purpose of this research is to describe the signs contained in the play script related to signs related to women in the play script “Domba-domba Revolusi”. The method in this research is descriptive qualitative using Roland Barthes’ semiotic theory. The data in this study are phrases, words, or sentences that contain signs in the drama script and are obtained by reading, listening, and recording techniques. The results of this study found that the signs contained in the play are related to the meaning of women, struggle, and socio-politics, among others: women’s independence, women and past trauma, women’s courage, including signs related to women’s self-esteem. This research shows that women in the revolutionary period had independence and a central role, not only subject to social construction but able to make their own decisions and influence their surroundings in accordance with the spirit of the revolution.